Burnout syndrome in dermatology residents: A cross-sectional study - Asem M Shadid; Batal M Aldosari; Abdullah M Algarni; Abdulmajeed Bin Dahmash; Saad Altalhab; Ruaa Alharithy (Wolters Kluwer Medknow Publications, 2022)
Background: Burnout is defined by three dimensions: emotional exhaustion (EE), depersonalization (DP), and low personal feelings of achievement (PA). It is a prolonged response to chronic emotional and interpersonal stressors on the job. If unrecognized, the costs to the health-care system can be enormous. Purpose: The aim of this study is to investigate the prevalence of burnout levels and predictors among dermatology residents and the risk factors associated with it. Methods: Validated measure of burnout (Maslach Burnout Inventory-Human Services Survey), alongside the possible risk factors of burnout, was distributed to all dermatology board training residents in all affiliated centers in Riyadh, Saudi Arabia. The response rate was 96.2% with 51 residents completing the survey out of 53. Results: High EE was present in 41.2% of dermatology residents, a low sense of PA in 45.1%, while high DP was the least prevalent at 13.7%. Satisfaction with career was significantly associated with risk of high EE (odds ratios [OR] = 0.61, 95% Confidence interval [CI] = 0.15-22.3), risk of high DP (OR = 0.34, 95% CI = 0.08-0.316), and risk of low PA (OR = 0.86, 95% CI = 0.52-6.1). The average number of sleeping hours was also associated with risk of high EE (OR = 0.87, 95% CI = 0.54-3.88), risk of high DP (OR = 0.76, 95% CI = 0.5-1.41), and risk of low PA (OR = 0.86, 95% CI = 0.52-6.1). Our findings report high over all burnout in 7.8% of the respondents. Conclusion: EE and feelings of low PA were seen at a high rate among dermatology residents, while DP was the least prevalent across all burnout dimensions. Average daily sleeping hours alongside satisfaction with life/work balance, career, and salary showed a statistically significant association with DP, low PA, EE, and overall burnout. Protected time to pursue academic interests, for example, research and teaching, and a fair distribution of on-call hours per month, as well as a number of clinics per week may explain the rate of burnout in our study. These findings can be applied in the improvement of training programs to reduce the burnout rate among residents.